HUBUNGAN ANTARA MINAT BERWIRAUSAHA DAN KREATIVITAS - Vivien Datania; Nurdin Nurdin; Darwin Bangun (FKIP Unila, 2014)
The problem in this study is the lack of interest and entrepreneurial creativity of Economic Education ’s Students at University of Lampung. The purpose of this study was to determine the relationship between interest in entrepreneurship and entrepreneurial creativity with entrepreneurs force for Students of Economics of Education 2010, University of Lampung. The population in this study are students of Economics, University of Lampung Education class of 2010 with total number 84 students. By using probability sampling Slovin formula obtained sample 69 people. Based on the analysis of the research results obtained show that, (1) there is positive relationship between the perpetrator Interests Entrepreneurship Entrepreneurial students, (2) there is positive relationship between the perpetrator Entrepreneurial Creativity Entrepreneurial Students, (3) there is positive relationship between entrepreneurship Interests with Entrepreneurial creativity with Student Entrepreneurial Performers. Masalah dalam penelitian ini adalah kurangnya minat dan kreativitas wirausaha mahasiswa Pendidikan Ekonomi Universitas Lampung. Tujuan penelitian ini adalah untuk mengetahui hubungan antara minat berwirausaha dan kreativitas wirausaha dengan pelaku wirausaha Mahasiswa Angkatan 2010 Pendidikan Ekonomi Universitas Lampung. Populasi dalam penelitian ini adalah mahasiswa Pendidikan Ekonomi Universitas Lampung angkatan 2010 dengan jumlah siswa keseluruhan 84 orang. Dengan menggunakan rumus Slovin dengan probability sampling didapat sampel sebanyak 69 orang. Berdasarkan analisis diperoleh hasil penelitian yang menunjukan bahwa, (1) ada hubungan yang positif antara Minat Berwirausaha dengan Pelaku Wirausaha Mahasiswa, (2) ada hubungan yang positif antara Kreativitas Wirausaha dengan Pelaku Wirausaha Mahasiswa, (3) ada hubungan yang positif antara Minat Berwirausaha dengan Kreativitas Wirausaha dengan Pelaku Wirausaha Mahasiswa.Kata kunci: kreativitas wirausaha, minat bewirausaha, pelaku wirausaha.